The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5812/aapm.23149
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reciting the Word “Allah” on Pain Severity After Coronary Artery Bypass Graft Surgery: A Randomized Clinical Trial Study in Iran

Abstract: Background:One of the most expressed complains following coronary artery bypass graft (CABG) surgery is chest wall pain. Due to side effects of opioids used commonly for pain relief after heart surgeries, it is important to use low-cost and non-pharmacological methods independently or combined with palliatives to alleviate pain and consequently prevent undesirable drug adverse effects.Objectives:This study aimed to investigate the effect of Hazrate Zahra’s praises, which is one of the most known praises among M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 24 publications
1
30
1
5
Order By: Relevance
“…A study by Nasiri et al on the effects of reciting the word "Allah" on pain severity after coronary artery bypass reported a significant reduction of pain severity in the first three days after surgery. 3 Another study by Beiranvand et al on the effects of prayer meditation on postoperative pain and anxiety showed that there was significant reduction of postoperative pain in caesarean section patients. 4 Another non-pharmacological means of pain intervention is music therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Nasiri et al on the effects of reciting the word "Allah" on pain severity after coronary artery bypass reported a significant reduction of pain severity in the first three days after surgery. 3 Another study by Beiranvand et al on the effects of prayer meditation on postoperative pain and anxiety showed that there was significant reduction of postoperative pain in caesarean section patients. 4 Another non-pharmacological means of pain intervention is music therapy.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of Islam, recitation of the word "Allah" is very important and is considered equal to a prayer (18). According to recent scientific results, recitation of the word "Allah" has effective impacts on medical conditions including postoperative and burninduced pain (18,19), burn-induced anxiety (17), and postoperative vital signs (19).…”
Section: Introductionmentioning
confidence: 99%
“…This result is congruent with some previous studies. Dhikr therapy could reduce the pain experienced by patients after surgery (Haryani, Arifudin, & Nurhayati, 2015;Beiranvand, Noparast, Eslamizade, & Saeedikia, 2014), AMI patients (Nasiri et al, 2014), and primigravida women who experienced depression (Wahyuni et al, 2018). The decreasing pain scale is related to the patients' psychological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One complementary therapy which might be used to reduce the cardiac chest pain is Dhikr therapy. Some studies have shown the effect of Dhikr therapy in the clinical setting (Nasiri, Fayazi, Ghaderi, Naseri, & Adarvishi, 2014;Sulistyawati, Probosuseno, & Setiyarini, 2019;Wahyuni, Soejoenoes, Putra, & Syukur, 2018). Sulistyawati et al (2019) used Dhikr therapy to reduce anxiety in patients suffering from cancer.…”
Section: Introductionmentioning
confidence: 99%